EFISIENSI KEUNTUNGAN USAHATANI BAWANG MERAH DI KABUPATEN NGANJUK: PENDEKATAN STOKASTIK FRONTIER - Hasan, Fuad (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2019)
This study aims to determine theprofitefficiency and potential profits-loss of shallot farming in Nganjuk Regency. Primary data was collected by questionnaire guidance. The numbered of respondents are 90 farmers who came from four sub-districts are Sukomoro, Rejoso, Bogor, and Gondang. Data analysis used stochastic frontier analysis (SFA) with profit function. The result of analyzed shows that the averageof profitefficiencywas0.614 and the profit potential lost due to the inefficiency was Rp 17.567.025,32 / hectareKeywords:shallot, profit efficiency, profit-loss